Stock-Scion Interaction Effect on the Quality of Planting MaterialsofRubber (Heveabrasiliensis) - Raveendra, H.; Sripala, S.; Priyani, S. (University of Jaffna, 2020)
Stock effect on scion performances is a critical factor to produce quality planting materials, in bud grafting, for rubber industry. Selection suited stock- scion combinations should be done to have a clonal authenticity relevant to a clone for generations. This study was contributed to identify successful stock scion combination/s to produce vigorous plants. Research activities were conducted using 12 budded plant combinations, belonged to most popular seed bearers and clones, as treatments of four stock types viz. seedling, PB 86, RRIC 102, RRIC 121 and three scion types viz. PB 86, RRIC 102 and RRIC 121 at a site located in RRISLSubstation Moneragala (IL1c). Treatments were arranged as two factor factorial experiment in the Randomized Complete Block Design (RCBD) and measurements were taken at monthly intervals up to two leaf whorl stage. Stock diameter and height, scion shoot diameter and height, time taken for bud breaking, leaf chlorophyll content, leaf area, specific leaf weight and leaf thickness were recorded before and after bud grafting. Data was analyzed using SAS (version 9.1) package. And significant means were separated using Duncan Multiple Range Test (DMRT) at the 5% probability level. Results revealed, that clone RRIC 102 is the most suitable stock to increase scion growth, leaf area and specific leaf weight whilst stock type not effect for chlorophyll content and leaf thickness.Although, clonal variations were recorded for leaf area, leaf thickness, specific leaf weight and chlorophyll content of leaves irrespective to the stock type. However, significant stock - scion combinations were identified and further studies are needed to recommend suitable stocks for higher yield and adaptability to the different agro-climatic regions.
Keywords: Bud grafting; Compatibility; Hevea brasiliensis; Planting materials; Stock scion combinations